TH3.2 Audit of acute lower GI bleed admissions - outcomes and management. (9th August 2022) - Sami, Sharukh; Hemadasa, Niroshini A; Loh, Cheryl; DeCruz, Antony; Mirza, Muhammad
Abstract: Background: Lower GI bleeding (LGIB) is a common surgical emergency. The British Society of Gastroenterology (BSG) in 2019 developed a UK national guideline on the management of LGIB. Our aim is to audit the current practice and standards for patients admitted with LGIB. Methods: This retrospective audit identified patients presenting to the Emergency department and Surgical assessment unit between September 2020 to February 2021 with LGIB. The shock index and Oakland score (OS) at first presentation were calculated. Results: A total of 27 patients satisfied the inclusion criteria. Average age of patients was 64.7 years. Three patients had an OS of ≤8 with 1 patient being hospitalised. 21 patients had an OS of >8 and 7 out of the 21 patients were discharged instead. 14 patients (51.8%) were on anticoagulants/antiplatelets of which 1 was on dual antiplatelet therapy. 10 patients had their drugs suspended appropriately and 2 did not. Eight patients were referred for OP endoscopy. Conclusion: We found that improvements can be made with respect to suspension of anticoagulant and antiplatelet drugs and duration to colonoscopy. A more pragmatic approach to both intervention and interval to endoscopy may have to be applied due to service constraints. A checklist has been developed based upon the guidelines to Triage patients as stable or unstable bleed at admission Recommend admission or discharge Guide decisions regarding suspension and re-commencement of antiplatelet and anticoagulants We plan to re-audit the parameters prospectively after 3 months from the roll-out of the checklist.